The effect of DIC parameters in the measurement of stress intensity factors Kı and Kıı / Lenny Iryani ... [et al.] - Iryani, Lenny (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2013)
In the present work, the effect of several Digital Image Correlation (DIC) parameters to the accuracy of the Stress Intensity Factors (K), was investigated. The values of Kı and Kıı were estimated in a three point bend specimen from the displacement field values around the crack tip obtained experimentally by using the DIC technique, using non-linear least square technique together with Taylor's expansion. It was found that some DIC parameters i.e. subset and template area should be carefully chosen in order to obtain an accurate result. The results showed that by setting the subset and the template edge length ratio to be 0.2 - 0.6, the K of mode I and mode II were in good agreements compared to the finite element results. The maximum difference of Kı is 1.9% and Kıı is 4.6%.